Avaliação do crescimento de Egeria densa Planch. submetidos a diferentes concentrações de óleo diesel - Scardovelli, Alana Moraes (Universidade Federal de São Carlos, 2025)
Petroleum is a substance composed of hydrocarbons, with diesel oil being a widely used example. Diesel oil can reach natural environments and cause negative impacts, such as changes in germination and growth patterns of some plant species. In this context, this study aimed to evaluate the effect of different concentrations of diesel oil S10 on the growth of a submerged aquatic macrophyte (Egeria densa), popularly known as Elodea. This study hypothesizes that E. densa, when exposed to diesel oil S10, will have its growth affected, resulting in a decrease in its growth coefficients. Fragments of E. densa were planted in polypropylene plastic cups containing attachment substrate and covered with gravel. For each treatment, seven fragments were randomly distributed in the bioassays. After this period, solutions of diesel oil S10 at concentrations of 0.5% (v/v), 2% (v/v), and 4% (v/v) were added to the bioassays, forming treatments T0.5, T2, and T4, respectively. Growth evaluation was performed weekly for eight weeks. The growth of E. densa in treatments T2 (p < 0.05) and T4 (p < 0.001) was significantly different from the control. The presence of diesel oil S10 altered the growth parameters from the 7th week onwards, with severe changes in growth, especially in treatments T2 and T4, making these environments unfavorable for plant growth, resulting in chlorosis and macrophytes death. The results suggest chronic effects on plant physiology or indirect effects caused by modification of the prevailing growth conditions.
Evaluation of growth of Egeria densa Planch. Subjected to different diesel oil concentrations
Keywords: Macrófita; Modelagem matemática; Crescimento; Bioensaio; Contaminante; Macrophyte; Mathematical modeling; Growth; Bioassay; Contaminant; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS